The Cost of Plastics in Compost - Yesaya, Mabvuto; Mpanang'ombe, Wrixon; Tilley, Elizabeth (Frontiers in Sustainability, 2021)
In urban Blantyre, there is ample green-waste and widespread interest in compost, but the feedstock is often contaminated with plastics. If composting is going to become more widely implemented, it must be profitable and ideally, competitive with chemical nutrients, however the time and cost associated with plastics removal is currently a bottleneck to profitability. In this study we investigated the financial sustainability of compost production using a Time-Driven Activity-Based Costing method over 16-weeks to identify the types and duration of each activity required. Combining these data with capital and operating costs, we then modelled the profitability of the facility to identify cost-bottlenecks and to determine scenarios that would lead to improved profitability. The results show that it took 1 hour 50 minutes of labour to produce 1 sixty-five-liter (0.065 m3) bag of compost. A total of 12.3% of the active labour time was spent sorting out plastics from the organic waste before composting, during composting and from the finished product before packaging. Until similar work is published on the topic, these values cannot be evaluated as being either optimal or wasteful, but rather, serve as a baseline against which future interventions—e.g. source separation, especially at markets can be evaluated. Though based in Malawi, the documented and modelled costs can be converted and scaled by other entrepreneurs/agencies who are interested in estimating the financial feasibility of composting in their own context.